A reforma petroleira do governo Chávez e o processo de mudanças econômicas e sociais na Venezuela - Silva, Paulo Daniel e (2009)
The objective of this work is to reform the Venezuelan oil in 2001 and its importance for economic and social development in the last period. The procedure is used to search literature and analysis of data released by public agencies responsible for programs of economic and social development. As an economy dependent on oil, Venezuela since 1943, conducting a search process of industrialization by import substitution, but because it is an unearned income economy has never in fact achieve it. With the rise of Hugo Chávez in the conduct of the Venezuelan state in 1999, still without a clear and defined project of economic and social development in the beginning of his government, but understand the need and importance of conducting institutional changes, beginning with the Reform Constitutional and oil, and that from 2001, is the state of exploitation and control of oil resources, while develop again the OPEC (Organization of Petroleum Exporting Countries) and again the oil price in international market returns filling up the country foreign exchange. From 2003, after the coup d'état, there are two main development funds, exchange controls and performs the control of capital, it is used in international reserves and surpluses of oil revenue to place in the economic development process and social in this country. It can be concluded that oil was essential to the reform process initiated development. However, with the eruption of the international financial crisis and reduction of prices of oil, obviously the crisis hit the country, but with the abundance of foreign exchange gains, it is an important source of funding for continuing the process of industrialization by substitution of import